Endothelial and Autonomic Functions in Patients with Migraine. Issue 2 (11th October 2019) - Dogru, Mehmet Tolga; Dilekoz, Ergin; Alpua, Murat; Eroglu, Oguz; Kandemir, Hüseyin; Alp, Caglar; Bolay, Hayrunnisa
Abstract: Objective: It has been shown that patients with migraine have endothelial dysfunction. Migraine patients with aura, especially, have more clinical manifestations of autonomic nervous system dysfunction. We aimed to evaluate the endothelial and autonomic functions in migraine patients during both migraine headache attack and headache-free periods. Design: This was a cross-sectional, randomized study. Subjects and Methods: A total of 130 participants (67 male and 63 female patients, minimum age = 19 years, maximum age = 71 years, mean age = 38.8 ± 12.2 years) were enrolled into the study. For the statistical evaluation of data, we classified the participants of the study as follows: group 1: headache (+) aura (+); group 2: headache (+) aura (−); group 3: headache (−) aura (+); group 4: headache (−) aura (−). Noninvasive evaluation of endothelial function was performed by flow-mediated dilation (FMD) and pulse wave analysis methods. Heart rate variability measurements were used for noninvasive evaluation of autonomic functions. Results: Group 1 had a higher FMD ratio than the control group, group 3, or group 4 ( P  < 0.001, P  < 0.001, and P  = 0.003, respectively). Group 4 had lower FMD ratio levels than the other migraine groups and or the control group ( P  < 0.001). Group 3 had the highest high-frequency (HF) power levels among all migraine groups ( P  < 0.001). Group 2 had higher low-frequency/HF ratio values than other migraineurs ( P  < 0.001). Conclusions: We concluded that endothelial dysfunction and headache are closely related. Additionally, higher parasympathetic tonus might be associated with the presence of aura.